2017
DOI: 10.1093/nar/gkx593
|View full text |Cite
|
Sign up to set email alerts
|

Unencumbered Pol β lyase activity in nucleosome core particles

Abstract: Packaging of DNA into the nucleosome core particle (NCP) is considered to exert constraints to all DNA-templated processes, including base excision repair where Pol β catalyzes two key enzymatic steps: 5′-dRP lyase gap trimming and template-directed DNA synthesis. Despite its biological significance, knowledge of Pol β activities on NCPs is still limited. Here, we show that removal of the 5′-dRP block by Pol β is unaffected by NCP constraints at all sites tested and is even enhanced near the DNA ends. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Such de-compaction may increase the access of Polβ to the damage site and enhance the enzymatic activity towards our NCP models. Moreover, an increase in Polβ activity after damage dislocation towards the blunt ends has been documented (72). Nevertheless, the proximity of the single-strand break to the blunt ends of DNA duplexes may start protein–protein competition for the substrate between PARP1 and Polβ.…”
Section: Discussionmentioning
confidence: 99%
“…Such de-compaction may increase the access of Polβ to the damage site and enhance the enzymatic activity towards our NCP models. Moreover, an increase in Polβ activity after damage dislocation towards the blunt ends has been documented (72). Nevertheless, the proximity of the single-strand break to the blunt ends of DNA duplexes may start protein–protein competition for the substrate between PARP1 and Polβ.…”
Section: Discussionmentioning
confidence: 99%
“…Removal and repair of aberrant bases are dramatically impaired in the context of chromatinized DNA [9][10][11][12]36 . It has been suggested that for efficient repair within chromatin to take place, BER needs to be associated with essential nuclear processes, such as transcription 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Association of AAG with transcription elongation could thus, in addition to enabling efficient removal of aberrantly methylated bases, serve as an important novel layer of gene expression control. 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the location of the substrate in the nucleosome, DNA glycosylases and APE1 have comparable activity on nucleosome substrates as with DNA, whereas some sites are completely inhibitory (3134). The gap-filling activity of Pol β with nucleosome substrates is inhibitory (18,31,3538). A question remains if BER enzymes can scan nucleosomal DNA to locate substrates and/or scan pass them.…”
Section: Processive Searching In Vivomentioning
confidence: 99%